A perception and imaging framework for far-range frequency-division-multiplexed computational imaging. Issue 8 (3rd August 2022) - Wu, Zhenhua; Huan, Sha; Zhang, Man; Sheng, Jialian; Pan, Xueli; Chen, Wei
ABSTRACT: So far, implementations of frequency-diverse computational framework with metamaterial element have used a frequency sweep across the operating frequency band, where the driving waveguide mode is coupled to subsets of the resonant elements at a corresponding excitation frequency. Scene information interrogating and processing efficiency are relatively confined in current imaging system especially for far-range imaging scenarios. Here, we implement frequency-division methods to parallelize computational imaging (CI). This concept multiplexes the modes in the frequency domain where different subsets of the resonant metamaterial elements are simultaneously excited by wideband multicarrier waveforms, allowing the scene to be encoded with different spatially diverse radiation patterns. Besides, we present a unified fast perception and processing framework for far-range imaging purpose. The proposed technique marries communications concepts to computational imaging, achieving a key development due to the limitations imposed by massive amount of data and burdensome computation. Numerical simulations with the measured radiation field pattern data are conducted to verify the effectiveness the technique.